Peningkatan Hasil Belajar Siswa Pada Materi Manusia Makluk Pribadi Dengan Model Problem Based Learning Fase E Kelas X SMAN 1 Palangka Raya - Adriana Tamo Ina; Hartutik Hartutik (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
This research was conducted on Catholic students in class X at SMAN 1 Palangka Raya because the researcher experienced that the learning outcomes of the students were not optimal. Theerefore this study aims to improve the learning outcomes of Catholic students in Catholic Religion subjects, in class X, with the Problem Based Learning model. The object of observation in this study was cognitive student learning outcomes and the application of the elements of faith and morality to humans (Pancasila Student Profile). The outcomes were: in cycle I, only 18% included the proficient category, 45,45% included the proficient category, 33.4% included the appropriate category. Whereas in cycle II students who reached the proficient category reached 64%, the proficient category 36% and the feasible category 0%. Observational data related to the application of moral elements to humans in cycles I and II show that, on average, the achievement of the P5 indicator that has been determined by the researcher has increased by 45%. This it can be concluded that the application of the PBL model contributes positively to improving student learning outcomes in class X SMAN 1 Palangka Raya on the theme Human Beings Personal